2017
DOI: 10.4186/ej.2017.21.4.259
|View full text |Cite
|
Sign up to set email alerts
|

Essential Feature Extraction of Photoplethysmography Signal of Men and Women in Their 20s

Abstract: Abstract. This study aims to extract the essential features of Photoplethysmography (PPG) signal of men and women in healthy subjects using Power Spectral Density (PSD) and Detrended Fluctuation Analysis (DFA). A PPG instrument was used to obtain the PPG signal of 15 men and 15 women. Using PSD, four frequency bands were selected to divide the spectral component. The areas within the frequency bands relative to the total area were computed as features of the signals. Furthermore, using DFA, the average fluctua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…After decryption, the low‐pass filter with cutoff frequency of 10 Hz is used to filter the decrypted PPG signal to remove the unwanted high‐frequency noises and to strengthen the pulsatile components of PPG signal. The decrypted PPG signals require to have the reliable and lossless performance for further time‐domain PPI , HR , and RI analyses for evaluating diabetic neuropathy, myocardial dysfunction, CVD, and cardiac rhythm [43, 44]. HR is the number of heartbeat in a minute (beats per minute, bpm) and can be estimated by HR=fs|peak(t+1)peak(t)|×60 where the term |peak( t + 1) – peak( t )| is the interval between two peaks (PPI), as shown in Figure 3, t = 1, 2, 3, …, N p – 1, N p is the peak number, which indicates a cardiac beat‐to‐beat interval of PPG signal, and f s is the sampling rate ( f s ≈ 1.04).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After decryption, the low‐pass filter with cutoff frequency of 10 Hz is used to filter the decrypted PPG signal to remove the unwanted high‐frequency noises and to strengthen the pulsatile components of PPG signal. The decrypted PPG signals require to have the reliable and lossless performance for further time‐domain PPI , HR , and RI analyses for evaluating diabetic neuropathy, myocardial dysfunction, CVD, and cardiac rhythm [43, 44]. HR is the number of heartbeat in a minute (beats per minute, bpm) and can be estimated by HR=fs|peak(t+1)peak(t)|×60 where the term |peak( t + 1) – peak( t )| is the interval between two peaks (PPI), as shown in Figure 3, t = 1, 2, 3, …, N p – 1, N p is the peak number, which indicates a cardiac beat‐to‐beat interval of PPG signal, and f s is the sampling rate ( f s ≈ 1.04).…”
Section: Methodsmentioning
confidence: 99%
“…After decryption, the low-pass filter with cutoff frequency of 10 Hz is used to filter the decrypted PPG signal to remove the unwanted high-frequency noises and to strengthen the pulsatile components of PPG signal. The decrypted PPG signals require to have the reliable and lossless performance for further timedomain PPI, HR, and RI analyses for evaluating diabetic neuropathy, myocardial dysfunction, CVD, and cardiac rhythm [43,44]. HR is the number of heartbeat in a minute (beats per minute, bpm) and can be estimated by…”
Section: Evaluation Of the Decryption Performances For Clinical Appli...mentioning
confidence: 99%
“…(6) Detrended Fluctuation Analysis (DFA) Detrended Fluctuation Analysis is a time-domain analysis of a signal. DFA is a statistical method to compute correlations that have a long range in a time series [86]. An integrated time series can be calculated by the following formula:…”
Section: Mathematical Details Of Ppg Featuresmentioning
confidence: 99%
“…Recent research studies have shown the applications of PPG analyzed in the frequency domain for blood pressure estimation and gender identification implying that it might be useful to analyze PPG in frequency domain [42,43]. The frequency range of PPG signals is low and hence we focus only on 0-5 Hz range.…”
Section: Spectrogram Deep Learning Featuresmentioning
confidence: 99%